The Effects of Fractions from Shiitake Mushroom on Composition and Cariogenicity of Dental Plaque Microcosms in an In Vitro Caries Model. (14th September 2011) - Zaura, Egija; Buijs, Mark J.; Hoogenkamp, Michel A.; Ciric, Lena; Papetti, Adele; Signoretto, Caterina; Stauder, Monica; Lingström, Peter; Pratten, Jonathan; Spratt, David A.; Wilson, Michael
Abstract : The aim of the current study was to investigate the anticariogenic potential of the (sub)fractions obtained from the edible mushroom shiitake ( Lentinula edodes ) in in vitro caries model. We used a modified constant depth film fermentor (CDFF) with pooled saliva as the inoculum and bovine dentin as a substratum. The test compounds were low molecular weight fraction (MLMW) of the shiitake extract and subfractions 4 and 5 (SF4 and SF5) of this fraction. Chlorhexidine (CHX) and water served as a positive and a negative control, respectively. Dentin mineral loss was quantified (TMR), microbial shifts within the microcosms were determined (qPCR), and the acidogenicity of the microcosms was assessed (CIA). From the compounds tested, the SF4 of shiitake showed strong inhibiting effect on dentin demineralization and induced microbial shifts that could be associated with oral health. The acid producing potential was increased, suggesting uncoupling of the glycolysis of the microbiota by the exposure to SF4. In conclusion, the results suggest that SF4 of shiitake has an anticariogenic potential.